Health data protection - The experience of the Hellenic Data Protection Authority - Λάτσιου (Charikleia Latsiou) Χαρίκλεια (Bioethica, 2017)
The presentation focuses on the complex issue of data protection concerning privacy issues that arise especially when health data are processed. In order for the audience to better understand the legal issues of these processing, definitional issues are examined mainly in the light of the new European legal framework on the protection of personal data (General Regulation 2016/679). Subsequently, the presentation examines key issues of certain types of processing mainly referring to: a) lawfulness, concerning the specified, explicit and legitimate purposes of processing, b) access to files of personal data, c) confidentiality and security of the processing and d) the meaning of the data subject’s consent for the legitimate processing of personal data. The main purpose of the presentation is to illuminate definitional issues that are deemed to be of high importance for the effective protection of personal data.